Review of MRI positioning devices for guiding focused ultrasound systems - Yiallouras, Christos; Damianou, Christakis A. (My University, 2015)
Background: This article contains a review of positioning devices that are currently used in the area of magnetic resonance imaging (MRI) guided focused ultrasound surgery (MRgFUS). Methods: The paper includes an extensive review of literature published since the first prototype system was invented in 1991. Results: The technology has grown into a fast developing area with application to any organ accessible to ultrasound. The initial design operated using hydraulic principles, while the latest technology incorporates piezoelectric motors. Although, in the beginning there were fears regarding MRI safety, during recent years, the deployment of MR-safe positioning devices in FUS has become routine. Many of these positioning devices are now undergoing testing in clinical trials. Conclusion: Existing MRgFUS systems have been utilized mostly in oncology (fibroids, brain, liver, kidney, bone, pancreas, eye, thyroid, and prostate). It is anticipated that, in the near future, there will be a positioning device for every organ that is accessible by focused ultrasound.
Keywords: MRI; Brain; Prostate